Reversal in fatigued athletes of a defect in interferon γ secretion after administration of Lactobacillus acidophilus. Issue 4 (23rd March 2006) - Clancy, R L; Gleeson, M; Cox, A; Callister, R; Dorrington, M; D'Este, C; Pang, G; Pyne, D; Fricker, P; Henriksson, A
Abstract : Background: Fatigue and impaired performance in athletes is well recognised and has been loosely linked to "overtraining". Reduced concentration of IgA in the saliva and increased shedding of Epstein Barr virus (EBV) have been associated with intense training in elite athletes. Objective: To determine whether athletes presenting with fatigue and impaired performance had an immune defect relevant to defective containment of EBV infection, and whether a probiotic preparation ( Lactobacillus acidophilus ) shown to enhance mucosal immunity in animal models could reverse any detected abnormality. Results: The fatigued athletes had clinical characteristics consistent with re-activation of EBV infection and significantly (p  =  0.02) less secretion of interferon (IFN) γ from blood CD4 positive T cells. After one month of daily capsules containing 2 × 10 10 colony forming units of L acidophilus, secretion of IFNγ from T cells had increased significantly (p  =  0.01) to levels found in healthy control athletes. A significant (p  =  0.03) increase in salivary IFNγ concentrations in healthy control athletes after the one month course of L acidophilus demonstrated in man the capacity for this probiotic to enhance the mucosal IFNγ concentration. Conclusion: This is the first evidence of a T cell defect in fatigued athletes, and of its reversal following probiotic therapy.